The Role of Playing Musical Instruments in Self‐Perception, Self‐Efficacy, and Social Skills of Early Childhood - Akyurek, Gokcen; Gundogmus, Ezginur; Salar, Zeynep (Psychology in the schools, 2025)
Self‐perception, self‐efficacy and social skills are very important for children's development. Although it is known that playing musical instruments in early childhood has many benefits, the number of studies examining its relationship with self‐efficacy and self‐perception is limited. This study aimed to compare the self‐perception, self‐efficacy, and social skills of children who play a musical instrument and those who do not. The sample consisted of children aged 7–11 years, including 39 students attending music schools who play an instrument (mean age = 9.27 ± 1.48 years) and 40 students who do not play an instrument (mean age = 9.03 ± 1.46 years). Participants completed three standardized instruments: the Self‐Perception Profile for Children, the Self‐Efficacy Questionnaire for Children, and the Children's Self‐report Social Skills Scale. While there was a statistically significant difference between the groups in social skills and self‐perception scores ( p < 0.05), there was no significant difference in self‐efficacy ( p > 0.05). These findings highlight the potential role of playing musical instrument in promoting children's development, supporting its inclusion in early childhood programs. While self‐efficacy did not differ significantly between groups, the observed benefits in other developmental domains suggest that incorporating music education into early childhood and primary school programs may offer meaningful support for children's psychosocial growth. 'School‐based interventions aimed at supporting students' social‐emotional development can benefit from the integration of musical instrument playing, which fosters self‐expression, cooperation, and self‐confidence. Distinguishing between children who play musical instruments and those who do not during assessment can guide professionals in planning individualized interventions in school settings. Since children who play an instrument may have advantages in terms of self‐perception and social skills, their participation in the classroom environment can be supported, as they adapt to other children's learning.